Research Progress on the Mechanisms by Which Natural Active Ingredients from Edible and Medicinal Fungi Regulate Uric Acid Metabolism - WEN Jing, YIN Chaomin, FAN Xiuzhi, SHI Defang, YAO Fen, YU Wei, GAO Hong (Shipin Kexue)
Hyperuricemia (HUA) and gout are metabolic disorders caused by excessive levels of uric acid in the body. With the continuous improvement of living standards, the prevalence of HUA and gout has risen year after year, and patients with HUA or gout have become younger, posing a great threat to human health. Recent studies have found that certain natural active compounds in edible and medicinal fungi may have remarkable effects in alleviating HUA. This paper reviews the state-of-the-art research on the process of uric acid metabolism, the pathogenesis of HUA and gout, and the mechanisms through which major active components in edible and medicinal fungi regulate uric acid metabolism. The aim of this review is to provide a reference and guidance for the development and utilization of active compounds in edible and medicinal fungi.